2011
DOI: 10.1177/197140091102400418
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Body Stenting System for the Treatment of Osteoporotic Vertebral Compression Fracture: Follow-up at 12 Months in 20 Cases

Abstract: We describe our preliminary experience with the vertebral body stenting system (VBS) for the treatment of osteoporotic vertebral fracture or traumatic vertebral fracture showing our clinical results at 12 months follow-up. Twenty patients (16 women, four men, mean age 71 years): four with traumatic vertebral fracture (Magerl A1 fractures) and 16 with osteoporotic vertebral compression fracture (VCFs) resistant to conservative therapy, were treated by vertebral body stenting system (VBS) as follows: two at leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
4
26
1
Order By: Relevance
“…The final rate of symptomatic extrusions in our series was 1% which is lower than the 2.6% in VP and comparable with the 1.3% in BKP reported by Hulme [2]. Klezl had 2 asymptomatic leakages in 20 treated vertebral bodies and Muto had none [10,11]. Klezl pointed out the more difficult situation in osteoporotic bone where a slight and careful overfilling of cement should be aimed at for achieving a good interdigitation of cement with bone [10].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The final rate of symptomatic extrusions in our series was 1% which is lower than the 2.6% in VP and comparable with the 1.3% in BKP reported by Hulme [2]. Klezl had 2 asymptomatic leakages in 20 treated vertebral bodies and Muto had none [10,11]. Klezl pointed out the more difficult situation in osteoporotic bone where a slight and careful overfilling of cement should be aimed at for achieving a good interdigitation of cement with bone [10].…”
Section: Discussionsupporting
confidence: 82%
“…The procedural details of the intervention have been well described by Klezl and Muto [10,11]. In the current series, a transpedicular approach was chosen in 94 (OP 97) %, a lateral extrapedicular one in 6 (OP 3) % of the cases.…”
Section: Resultsmentioning
confidence: 99%
“…Pain relief is obtained in 90% of patients with a reduction of four points in the VAS evaluation and a reduction of 40% in the ODS score. 26 The mean vertebral kyphosis correction is $ 3.2 degrees with a segmental kyphosis of 5 degrees. Compared with BKP, there is a minor height reduction observed at follow-up, losing 0.8 degrees of vertebral kyphosis and 2.1 degrees of segmental kyphosis correction.…”
Section: Resultsmentioning
confidence: 97%
“…After removing duplicates and applying the exclusion criteria, five studies were finally included [16][17][18][19][20] (Fig. 1): two clinical trials [16,20] (one non-randomized [16]) and three observational prospective [18,19] and retrospective studies [17].…”
Section: Resultsmentioning
confidence: 99%
“…Three case series studies [17][18][19] were identified about effectiveness and safety of stentoplasty, two of them [18,19] retrospectively and one [17], prospectively. No data from these studies could be pooled because of missing data and no coincidence of follow-up time intervals.…”
Section: Stentoplasty: Effectiveness and Safety From Observational Stmentioning
confidence: 99%